Analysis of Illocutionary Speech Acts in Translating Quran Surah Luqman: A Literature Review - Manangin, Nelpia; Kasan, Yuslin; Hula, Ibnu Rawandhy N. (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
This study examines illocutionary acts in Surah Luqman of the Quran. The research method used is qualitative-descriptive, with the Quran as the primary data source and relevant secondary sources. The analysis of illocutionary acts is conducted to understand the communicative purposes contained in the verses of Surah Luqman. The results of the study show the presence of various types of illocutionary acts in Surah Luqman. One type is assertive acts, which relate to statements of a neutral nature. An example of a verse containing an assertive act is verse 6, which warns about the dangers of idle talk that misleads people from the path of Allah. Additionally, other illocutionary acts found in Surah Luqman include directive, commissive, expressive, and declarative acts. Each type of illocutionary act has implications and implicit messages that are important to understand in the context of Quranic translation. This study contributes to understanding the meanings and messages in Surah Luqman and illustrates the various illocutionary acts contained in the surah. This research can serve as a basis for further studies on Quranic pragmatics and contextual understanding in interpreting the verses of the holy Islamic scripture.